Association between preoperative neutrophil-to-lymphocyte ratio and the survival outcomes of esophageal cancer patients underwent esophagectomy: a systematic review and meta-analysis - Wu, Xun; Liu, SiJie; Li, FengWei; Chen, YingTai (Frontiers in Oncology, 2024)
Objectives: To assess the association between preoperative neutrophil to lymphocyte ratio (NLR) and the survival outcomes of esophageal cancer patients underwent esophagectomy, the latest and comprehensive systematic review performed. Methods: Related literature retrieved from PubMed, Web of Science, Embase, and Cochrane before January, 2024, according to the inclusion criteria. Outcomes measured were overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), and cancer-specific survival (CSS). Results: Eighteen studies with 6119 esophageal cancer patients were retained for analysis. Meta-analysis demonstrated that OS (HR: 1.47; 95% CI: 1.29, 1.67; P ＜0.00001), DFS (HR: 1.62; 95% CI: 1.29, 2.05; P ＜0.0001) and CSS (HR: 1.62; 95% CI: 1.29, 2.05; P ＜0.0001) were significantly shorter in the high NLR group compared with the low NLR group. In addition, meta-analysis revealed a similar RFS (HR: 1.47; 95% CI: 0.92, 2.35; P = 0.10) among the two groups. Subgroup analysis of OS and DFS based on mean/median age, NLR cut-off and region found that all subgroups remained significant difference between two groups. Conclusions: Among esophageal cancer patients underwent esophagectomy, preoperative NLR can be used as prognostic factor independently. High preoperative NLR is associated with poor prognosis. More large-scale, multicenter, prospective clinical studies are needed to further validate the relationship between preoperative NLR and prognosis of esophageal cancer.